Aqueous-mediated synthesis of 2-amino-7-hydroxy-4-aryl-4H-chromene-3-carbonitrile derivatives using triethanolamine: An effective basic organocatalyst - Farzaneh Mohamadpour (Sustainable Chemistry for the Environment)
A sustainable method for the effective and simple synthesis of derivatives of 2-amino-7-hydroxy-4-aryl-4H-chromene-3-carbonitrile is developed. The process makes use of a domino Knoevenagel-Michael cyclocondensation reaction. The reaction occurs at reflux in an aqueous solution using triethanolamine, a cheap and effective basic organocatalyst. This process makes use of sustainable chemical principles. Reactions go more rapidly, yielding good to exceptional results. It does not separate mixtures using the chromatographic process. This is an easy and inexpensive way. Reaction times range from 40 to 65 min, with an average of 47.81 min, while yields range from 72 % to 93 %, with an average of 85.06 %. It's also important to note that a variety of functional groups that give or remove electrons may be used with this approach, and yet retain a fast reaction rate and good to exceptional yields. The results show that, given very basic and effective reaction conditions, this approach is a fruitful one-pot procedure. The nature of the substituents has no bearing on the reaction. Because it combines multiple steps into a one-pot, it is both convenient and expedient.